Homeless children: Experiences and meanings of the environments they construct - Constanza Forero Pulido; álvaro Giraldo Pineda; Johana Victoria Martínez Hernández
Objective.This work sought to learn of the experiences of homeless children and understand the meanings they give to environments they construct within these spaces. The study took place in Medellín, Colombia in 2015. Methods. Ours was a qualitative research with ethnographic approach. Non-structured interviews and observations were conducted; a field diary was kept. Results. The street, although a space of public use, is converted by children into their private space; they carry in it almost all their activities and construct two big environments: that of the street that attracts and educates and that of the work that is transitory because it is performed to survive. These children dream with an ideal environment that allows them to live quietly. Conclusion. Children convert the street into a private place where they carry out their daily practices: socializing, working, sleeping, having fun, and relaxing, that is, a place of social construction.